Development of an eHealth Mindfulness-Based Music Therapy Intervention for Adults Undergoing Allogeneic Hematopoietic Stem Cell Transplantation: Qualitative Study - Sara E Fleszar-Pavlovic; Blanca Noriega Esquives; Padideh Lovan; Arianna E Brito; Ann Marie Sia; Mary Adelyn Kauffman; Maria Lopes; Patricia I Moreno; Tulay Koru-Sengul; Rui Gong; Trent Wang; Eric D Wieder; et al. (JMIR Formative Research)
Abstract BackgroundAllogeneic hematopoietic stem cell transplantation (allo-SCT) is an effective treatment for various hematologic cancers, though it often results in severe side effects and psychological distress, which can negatively impact health outcomes. Integrative therapies like mindfulness-based stress reduction (MBSR), mindfulness meditation (MM), and music therapy (MT) yield promising results in enhancing both psychosocial outcomes (eg, reducing anxiety and depression) and physiological adaptation (eg, decreasing inflammation) in cancer patients. ObjectiveWe developed and refined, using focus groups and environmental and field testing, an eHealth-delivered mindfulness-based music therapy (eMBMT) intervention aimed at improving health-related quality of life, symptom burden (ie, pain, fatigue, and sleep), disease activity (ie, chronic graft-versus-host disease, cytomegalovirus activation, and infections) and psychosocial (ie, depression, anxiety, and cancer-specific distress) and physiological adaptation (ie, inflammation and immune reconstitution) tailored to adults receiving allo-SCT. MethodseMBMT intervention content is grounded in MT, MM, and MBSR, developed by a multidisciplinary team, and adapted for adults undergoing allo-SCT. eMBMT content was refined through focus groups and usability and field testing. Focus groups used a semistructured interview guide, while field testing used the “think aloud” method. Usability was evaluated using the 30-item Usefulness, Satisfaction, and Ease of Use (USE) questionnaire. Descriptive statistics analyzed the USE questionnaire and participant characteristics, while rapid qualitative analysis was applied to focus groups and field-testing sessions. Survivors eligible to participate in the focus groups and usability and field testing were adults (>< ResultsDuring the focus groups, participants (n=11; ConclusionsThe eMBMT intervention is a comprehensive, user-friendly eHealth tool tailored to the unique needs of allo-SCT patients. The positive feedback and identified areas for improvement underscore its potential to enhance well-being, symptom management, and overall quality of life for cancer survivors. A future pilot randomized controlled trial will further evaluate the feasibility, acceptability, and preliminary efficacy of the eMBMT intervention in improving health-related quality of life, symptom burden, disease activity, and psychosocial and physiological adaptation.